Hamstring Musculotendon Dynamics during Stance and Swing Phases of High Speed Running - Chumanov, Elizabeth S. (2011)
INTRODUCTION: Hamstring strain injuries are common in sports that involve high speed running. It remains uncertain whether the hamstrings are susceptible to injury during late swing phase, when the hamstrings are active and lengthening, or during stance, when contact loads are present. In this study we used forward dynamic simulations to compare hamstring musculotendon stretch, loading and work done during stance and swing phases of high speed running gait cycles. METHODS: Whole body kinematics, EMG activities and ground reactions were collected as 12 subjects ran on an instrumented treadmill at speeds ranging from 80% to maximum (average of 7.8 m/s). Subject-specific simulations were then created using a whole body musculoskeletal model that included fifty-two Hill-type musculotendon units acting about the hip and knee. A computed muscle control algorithm was used to determine muscle excitation patterns that drove the limb to track measured hip and knee sagittal plane kinematics, with measured ground reactions applied to the limb. RESULTS: The hamstrings lengthened under load from 50% to 90% of the gait cycle (swing), and then shortened under load from late swing through stance. While peak hamstring stretch was invariant with speed, lateral hamstring (biceps femoris) loading increased significantly with speed, and was greatest during swing at the fastest speed. The biarticular hamstrings performed negative work on the system only during swing phase, with the amount of negative work increasing significantly with speed. CONCLUSION: We concluded that the large inertial loads during high speed running appear to make the hamstrings most susceptible to injury during swing phase when compared to stance phase. This information is relevant for scientifically establishing effective muscle injury prevention and rehabilitation programs.